Sustainable supply chain management practices and environmental performance in a developing country’s petroleum industry: the mediating role of operational performance - Ernest Mugoni; James Kanyepe; Marian Tukuta (International Business Logistics Journal)
Purpose: This study explores the impact of sustainable supply chain management practices (SSCMPS) on environmental performance within Zimbabwe’s petroleum industry. It also investigates the mediating role of operational performance in this relationship, addressing the growing environmental challenges and regulatory pressures faced by the industry. Methodology: A quantitative research approach was adopted, with data collected from 226 supply chain professionals. Structural Equation Modeling (SEM) using SmartPLS software was employed to analyse the relationships between SSCMPS, operational performance, and environmental performance. Results: The results demonstrate that SSCMPS positively influence environmental performance, with operational performance playing a significant mediating role. Among the SSCMPS, green purchasing and reverse logistics exhibit the strongest positive impacts, underscoring their critical importance in enhancing environmental outcomes and operational efficiency. The study is limited to Zimbabwe’s petroleum industry and relies on crosssectional data, which may restrict the generalisability of findings. Future Research: Future research could explore longitudinal studies or apply the model to other sectors and regions. The findings offer practical guidance for industry stakeholders on prioritising green purchasing and reverse logistics to improve both environmental and operational performance. By promoting sustainable practices within the petroleum supply chain, this study contributes to reducing environmental degradation and fostering sustainable development in developing economies. Research Contribution: This research contributes to the sustainability literature by developing a model that integrates SSCMPS with environmental and operational performance outcomes, emphasising the mediating effect of operational performance. It provides actionable insights for policymakers and industry leaders, particularly in the context of developing economies.   Received on: 19 February 2025 Accepted on: 26 March 2025 Published on: 07 May 2025